Unilateral shunt formation with thoracic aortic dissection in a whippet. (7th March 2014) - Cornelis, I.; Bosmans, T.; Doom, M.; Binst, D.; Van der Vekens, E.; Kromhout, K.; Cornillie, P.; Van Ham, L.
<x xml:space="preserve">Abstract</x> A three‐year‐old neutered male whippet was presented with intermittent, exercise‐induced paraparesis. Femoral pulses were bilaterally absent. Neurologic examination was suggestive of a thoracolumbar myelopathy. Blood pressure measurements revealed hypotension in both pelvic limbs, hypertension in the right thoracic limb and it was immeasurable in the left thoracic limb. Echocardiography was within reference limits. A clear vascular pulsation was palpable on the right ventral abdominal wall. Computed tomographic angiography revealed a dissection of the aortic wall between the left subclavian artery and the brachiocephalic trunk with subsequent thrombus formation. A shunt between the right internal thoracic, cranial and caudal epigastric arteries to preserve blood flow to the pelvic limbs was visualized. Necropsy was declined by the owner. This is the first case report describing the formation of a unilateral vascular shunt following a thoracic aortic occlusion, which presented as exercise‐induced paraparesis.